2017
DOI: 10.1136/jclinpath-2017-204370
|View full text |Cite
|
Sign up to set email alerts
|

There is still a role for cytology in the ‘liquid biopsy’ era. A lesson from a TKI-treated patient showing adenocarcinoma to squamous cell carcinoma transition during disease progression

Abstract: Non-small cell lung carcinoma harbouring epidermal growth factor receptor () mutation, usually progress after an initial response to tyrosine-kinase inhibitors (TKI). Liquid biopsy enables with a simple blood draw the accurate detection of p.T790M mutation, the most common resistance mechanism, avoiding the more invasive tissue re-biopsy. However, in a subset of cases, resistance mechanisms are more complex featuring both genetic and morphological changes. Here we report the case of a 67 years-old woman, affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Acquired polyclonal resistance in tumors and the development of new resistant tumor cell clones are consequential for treatment. It has previously been shown that liquid biopsy has the potential to further enhance our ability in longitudinal monitoring of dynamic clonal evolution of tumor cells during drug therapy . Tumor resistant mutations, specifically in breast cancer, can be divided into two subgroups.…”
Section: Utilization Of Liquid Biopsy For Breast Cancer In the Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired polyclonal resistance in tumors and the development of new resistant tumor cell clones are consequential for treatment. It has previously been shown that liquid biopsy has the potential to further enhance our ability in longitudinal monitoring of dynamic clonal evolution of tumor cells during drug therapy . Tumor resistant mutations, specifically in breast cancer, can be divided into two subgroups.…”
Section: Utilization Of Liquid Biopsy For Breast Cancer In the Clinicmentioning
confidence: 99%
“…It has previously been shown that liquid biopsy has the potential to further enhance our ability in longitudinal monitoring of dynamic clonal evolution of tumor cells during drug therapy. 197,198 Tumor resistant mutations, specifically in breast cancer, can be divided into two subgroups. One of these is the first-generation mutations developed during tumorigenesis, while the other is acquired mutations that could result in development of resistance.…”
Section: Primary Tumor Localization and Capturing Intra/intertumoramentioning
confidence: 99%
“…23 In addition, MET and HER2 amplification and over-expression (which create resistance by bypassing the EGFR signaling pathway) were seen in 15% to 20% of cases of resistance in one series, 9,12 another series reported resistance due to MET amplification in 3% of the cases, and due to HER2 amplification in 13% of the cases. [26][27][28][29][30][31][32][33] These cases were observed to retain their original EGFR mutation, three cases developed an addition mutation in Thr790Met of EGFR Exon 20, 30,31 whereas two cases harbored an addition PIK3CA mutation. Immunocytochemistry stains for Synaptophysin (d) and CD56 (e) were positive, supporting the diagnosis of small cell carcinoma [Color figure can be viewed at wileyonlinelibrary.com] carcinoma transformation, 5,12,13,[16][17][18] or squamous cell transformation.…”
Section: Case Descriptionmentioning
confidence: 96%
“…Molecular testing of the case discussed in this review and of the core biopsy cases reported in literature, performed at the time of TKI resistance acquisition, revealed retention of the same type of EGFR mutation detected in the initial diagnostic biopsies. [26][27][28][29][30][31][32][33] EMT manifests on the ultrastructural level by acquiring mesenchymal markers such as Vimentin and Fibronectin, and downregulating the expression of cellular junction proteins, such as Ecadherin and Gamma Catenin. 12 One year after TKI resistance acquisition, a third FNA was performed to monitor patient's disease progression.…”
Section: Case Descriptionmentioning
confidence: 99%
See 1 more Smart Citation